7.7k views
2 votes
*math please help* Simplify.

*math please help* Simplify.-example-1
User Hexfire
by
5.7k points

2 Answers

2 votes


Given : ((4x)/(5 + x))/((6x)/(x + 2))


\implies (4x)/(5 + x)*(x + 2)/(6x)


\implies (2)/(x + 5)*(x + 2)/(3)


\implies (2(x + 2))/(3(x + 5))


\implies (2x + 4)/(3x + 15)

User Mhorgan
by
6.8k points
5 votes

( (4x)/(5 + x) )/( (6x)/(x + 2) ) \\ = (4x)/(5 + x ) ( (x + 2)/(6x) )

= \frac{4x^(2) + 8x}{30x + {6x}^(2) } \\ = \frac{2x(2 {x} + 4) }{2x(3 {x}+ 15)} \\ = \frac{2 {x} + 4 }{3 {x} + 15}
User Marian Gibala
by
5.8k points